2011
DOI: 10.1007/s00340-011-4587-z
|View full text |Cite
|
Sign up to set email alerts
|

Fast and sensitive time-multiplexed gas sensing of multiple lines using a miniature telecom diode laser between 1529 nm and 1565 nm

Abstract: High-sensitive multi-species detection around 1550 nm using a modulated grating Y-branch, MG-Y, diode laser tunable between 1529 nm and 1565 nm is presented. The MG-Y diode laser is based on the Vernier effect of two modulated gratings, and exhibits quasi-continuous tuning over 36 nm. Multi-species detection is achieved by fast sequential scanning of single absorption lines of CH 4 , CO, C 2 H 2 , and CO 2 distributed over the tuning range of the diode laser. The laser wavelength is scanned about 10 GHz around… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 24 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…Due to the molecular properties of the analytes of interest, their absorption lines (especially for strong transition lines suitable for high sensitivity detection) are clearly separated and thus could not be easily covered by a single tunable laser source. With the dramatic improvement in novel light sources and optical or acoustic detectors, as well as signal recovery electronics, various sensing strategies based on the tunable laser absorption spectroscopy technique (TDLAS) have been developed for multigas detection, typically three or more gas species, such as the multiple laser light source scheme , and the time or frequency division multiplex detection method. , Over the past decades, quantum cascade lasers (QCLs) have been proven as attractive and promising light sources for developing gas sensors. The emitted wavelength within ten wavenumbers is usually obtained by either changing the injected current or the temperature of the gain element.…”
mentioning
confidence: 99%
“…Due to the molecular properties of the analytes of interest, their absorption lines (especially for strong transition lines suitable for high sensitivity detection) are clearly separated and thus could not be easily covered by a single tunable laser source. With the dramatic improvement in novel light sources and optical or acoustic detectors, as well as signal recovery electronics, various sensing strategies based on the tunable laser absorption spectroscopy technique (TDLAS) have been developed for multigas detection, typically three or more gas species, such as the multiple laser light source scheme , and the time or frequency division multiplex detection method. , Over the past decades, quantum cascade lasers (QCLs) have been proven as attractive and promising light sources for developing gas sensors. The emitted wavelength within ten wavenumbers is usually obtained by either changing the injected current or the temperature of the gain element.…”
mentioning
confidence: 99%
“…Traditionally, multilasers used in a multi-gas detection system will induce an optical interference effect, when a single photodetector was used without time-division multiplexing. , Thus, an interference test is necessary to verify the proposed MIR and NIR coupled gas sensor system. For this issue, an intermittent blocking experiment was performed.…”
Section: System Optimizationmentioning
confidence: 99%
“…Due to the molecular properties of the analytes of interest, their strong absorption lines suitable for high-sensitivity detection are clearly separated; therefore, it is almost impossible to achieve simultaneous measurement of CO, N 2 O, and CH 4 with a single laser in current TDLAS. Thus, multilaser-based gas sensor systems were usually employed to achieve detection of multi-gas species. For example, Santoni et al presented an evaluation of aircraft observations of CO 2 , CH 4 , N 2 O, and CO by combining a direct absorption pulsed quantum cascade laser spectrometer (QCLS) with three pulsed quantum cascade lasers. Kostinek et al reported simultaneous airborne in situ observations of CH 4 , C 2 H 6 , CO 2 , CO, and N 2 O using a quantum and interband cascade laser spectrometer.…”
mentioning
confidence: 99%
“…In particular, a MG-Y laser based on the Vernier effect of two multipeak Y-shaped grating reflectors to turn the wavelength widely has high power, high sidemode suppression ratio (SMSR), wide tuning range and short tuning time [3,4]. A MG-Y laser is a typical monolithic tunable semiconductor laser and has been applied widely in optical communication, spectrum analysis, and optical fiber grating interrogators, etc [5][6][7]. As the core element of the scanning laser interrogator for an optical fiber Bragg grating (FBG) sensor system, it has been used in a wide range of research and a wavelength resolution of about 1 pm and precision of about 2 pm has been achieved [8,9].…”
Section: Introductionmentioning
confidence: 99%